Framework for New Generation Web Form and Form Filling for Blind User - Kian, Kok Cheung; Edwin, Mit; Chong, Eng Tan (IEEE, 2011)
Blind users have very low vision to interact with the world. Information accessibility is always a problem to them. The traditional application form filling task can always be difficult for them to accomplish. In a lot of cases, they rely on Braille technology or assistant from a sighted people in order to fill the form. As the Internet gets popular with advancement in web technologies, web form has replaced a lot of the traditional printed form as a tool for information acquisition. Assistive technology has also been introduced to assist web form filling but there are still issues of web form that need to be solved in order to have a better experience in form filling. In this paper, an innovative framework to enable a better web form filling for blind user will be presented.